2022
DOI: 10.1039/d2sc02953g
|View full text |Cite
|
Sign up to set email alerts
|

Radical generation enabled by photoinduced N–O bond fragmentation

Abstract: Recent advances in synthetic chemistry have seen a resurgence in the development of methods for visible light-mediated radical generation. Herein, we report the development of a photoactive ester based on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Only the exo ‐methylene intermediate In ‐ 2b shows an absorption reaching the visible part of the spectrum, with a broad band ranging from 320–500 nm (maximum at 385 nm). It is therefore very likely that intermediate In ‐ 2b can be excited by visible light and hence its homolytic cleavage to the radical pair In ‐ 5 / In ‐ 6 (Scheme 7) may be induced [19] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the exo ‐methylene intermediate In ‐ 2b shows an absorption reaching the visible part of the spectrum, with a broad band ranging from 320–500 nm (maximum at 385 nm). It is therefore very likely that intermediate In ‐ 2b can be excited by visible light and hence its homolytic cleavage to the radical pair In ‐ 5 / In ‐ 6 (Scheme 7) may be induced [19] …”
Section: Resultsmentioning
confidence: 99%
“…It is therefore very likely that intermediate In-2b can be excited by visible light and hence its homolytic cleavage to the radical pair In-5/In-6 (Scheme 7) may be induced. [19] Summarizing the experimental facts, it is evident that the mechanistic scenario of the Boekelheide rearrangements of model compound 1 is quite complex. Depending on the conditions, the reaction can occur cleanly affording the expected rearrangement products, e. g., compound 2, essentially without side products.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…Herein we report the implementation of N -alkoxypyridinium salts in this process. Simple N -alkoxypyridinium salts can be readily prepared in one step and offer an electronically tunable HAT scaffold. , Finally, mechanistic evidence suggests that an electron-donor–acceptor (EDA) complex may be operable for activating the pyridinium reagents for certain electron-rich benzylic partners …”
mentioning
confidence: 99%
“…Lastly, pyridinium salts have been reported to participate in EDA complexes. ,,, Control experiments suggested that when HFIP is added as a cosolvent, an EDA complex could be operable, on the basis of the observation of product without photocatalyst and an observed bathochromic shift in the UV–vis spectra (Figure b). Presumably, the EDA complex facilitates oxidation of the arene, which triggers fragmentation of pyr-1 to release a methoxy radical.…”
mentioning
confidence: 99%
“…Herein, green light illumination under an anaerobic condition efficiently improves the photostability of CvFAP, which will facilitate it as an alternative to organic or inorganic catalysts for decarboxylation reaction. 10,18,[28][29][30][31] However, the conversion of real biowaste with CvFAP still remains very challenging. For instance, when producing sustainable aviation fuels from waste lipids, the matching of lipase and CvFAP activity needs to be considered to avoid acid inhibition to CvFAP.…”
mentioning
confidence: 99%